The satisfaction of residents on public facilities at Bandar Universiti : a case study of Seri Iskandar, Perak / Suwaibah Sahfie - Sahfie, Suwaibah (2020)
Public facilities are important element in residents’ area. The lack and dissatisfaction of public facilities can affect many things in the daily life of residents. All the public facilities must follow the guideline. Placement and location of public facilities are important to the residents. Provision of public facilities must be a comfort and safety, and strategic location, it can encourage social interaction to interact with the community and most important is public facilities must be located with walking distance and residential area safe from traffic. The aim of this study is to know the satisfaction of residents on public facilities at Bandar Universiti Seri Iskandar Perak also to recommendations the suggestion on improvement public facilities at residents’ area. All the suggestion is based on the observation and questioner that have been collected.